The Crisis of US-centric Globalization: Causes, Trends and Scenarios of Development - A. A. Kasantzev; V. M. Sergeev (Vestnik MGIMO-Universiteta)
Traditionally the processes of globalization and the issues of world politics related to hegemony are studied separately in the scientific literature. In this article the authors propose the synthesis of both of these approaches based on the model of transactional and innovative economy spatially structured as a system of “global gateways”. The globalization is conceived in the article as a process of reinforcement of network connections of different parts of the globe. The network is distributed unevenly around the world. The increase of globalization processes stimulates the strengthening of the network interactions and saturation of it with resources. The decline of the globalization we are witnessing at the moment results in the weakening of network relations. Spatial heterogeneity of globalization produces inequality in resource distribution on social as well as regional and country level. Due to this fact the system of global economy based on these gateways requires the stability of political institutes. In the 19th-20th centuries the system of maintenance of global stability (known in IR as hegemonic stability) was established. Increasing globalization provides the effective interaction between economic and political spheres. Declining globalization produces a gap between gateways’ demands for political stability and a hegemon’s ability to provide it. Recently the USA’s abilities as global hegemon have shrunk dramatically in relative terms as well as American electorate’s willingness to bear the costs of hegemony. Washington is unable to maintain stable functioning of “the rules of the game” neither separately, nor with its allies. This situation may be described as “the crisis of US-centric globalization”. The crisis of globalization relates to decline of international regimes, rise of uncertainty and conflicts on all levels of world politics. Presumably, it’s a long-term process. And at the end it may cause the establishment of new political form of economic globalization (e.g. transition to the model of hegemony of a group of superpowers, a scenario mostly close to generally accepted in Russia idea of multi-polar world), or emergence of a new hegemon (e.g. China).